Financial Gains and Moral Satisfaction as Key Factors for Greater Efficiency in the Field of Education - Vasiliki Brinia; Stavroula Leimoniti; Alexandros Dimos (MDPI AG, 2021)
The present study examines teachers' perceptions regarding moral satisfaction, financial gain and professional motivation in order to examine the relationship between these factors and their work efficiency. The degree of agreement and disagreement in the perceptions of 270 Primary Education teachers, regarding the extent to which their effectiveness at work is affected by the existence of the above factors, is studied, and the study was conducted in 31 primary schools in Greece. The size of the sample and the way the results are extracted is a key innovation of the research, as for the first time, the above concepts are quantified through the answers of those involved in education. Their answers are examined by the method of quantitative research and the statistical program IBM-SPSS 24. It appears that moral rewards, the relationship with their manager and colleagues and their degree of self-esteem are elements that, if increased and positive, lead to higher productivity in their work. The recognition of the overall offer of the teachers by colleagues, the manager, society and the state have a positive effect on the effectiveness of their work, while its lack reduces their motivation to be efficient.